DEI VERBUM “ALKITAB BUKU YANG TERBUKA” - Simeon Bera Muda (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
The Dogmatic Constitution Dei Verbum on Divine Revelation opens us towards God’s self revelation in the whole universe in order that all be gathered in Christ into full communion with the Triune God. This official teaching sees revelation as a dialogue of love, and a response in faith which is personal, dynamic, historical and centred on Christ and the Spirit. With this broad understanding of revelation, the Dei Verbum Constitution goes on to open up ways of interpreting the Scriptures and understanding how the Scriptures have been read in history (Tradition), thus opening up Bible study as the soul of theology, as well as the anima of prayer, liturgy and spirituality. The local Churches of Indonesia, Asia and the world, including the Society of the Divine Word (SVD), have responded to the invitation to participate in this divine dialogue of love by receiving God’s Word graciously and proclaiming it faithfully in daily life. The essay ends by noting the contribution of the Pontifical Biblical Commission, the Catholic Biblical Federation, Lembaga Biblica Indonesia, St. Paul’s Biblical Centre Ledalero, and the Biblical Apostolate Diocesan Commissions of Nusa Tenggara Ecclesial Province in Indonesia which have facilitated Bible sharing in grassroots communities. Kata-kata kunci: Wahyu, Alkitab, buku terbuka, animasi, mendengar, dialog, mewartakan, kepenuhan hidup, tradisi, penafsiran, doa, refleksi, aksi.